Analysis of Customer Satisfaction Levels With Pos Indonesia’s Courier Service After Transformation - Sunarto, Ziel Mahqwa; Permatasari, Bunga Indah; Widjaja, Andrianto (Universitas Prasetiya Mulya, 2025)
This study aims to analyze customer satisfaction levels with PT Pos Indonesia's courier services after the company underwent digital transformation in response to VUCA (Volatility, Uncertainty, Complexity, Ambiguity) business environment pressures and increased competition from private companies such as JNE, J&T, and TIKI. This study employs a quantitative approach using a survey method targeting 67 respondents who have used courier services after 2022. The population is unknown, so the sampling technique uses the Lemeshow formula. Data collection was conducted online from June 2–12, 2025, covering the national territory. Data was analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results indicate that customer satisfaction levels are high, but there are still areas that need improvement. Further research is recommended using a qualitative approach to explore internal factors and customer expectations in greater depth.